1995
DOI: 10.1002/ijc.2910630118
|View full text |Cite
|
Sign up to set email alerts
|

Loss of cell‐contact regulation and altered responses to autocrine motility factor correlate with increased malignancy in prostate cancer cells

Abstract: Tumor cell migration and proliferation in new organ environments are critical steps in cancer progression and can be modulated by tumor-and host-secreted molecules. Autocrine motility factor (AMF) is a tumor-secreted cytokine which regulates growth and motility by a receptor-mediated pathway. The AMF receptor, a 78-kDa cell surface glycoprotein (gp78). is regulated by cell contact in normal fibroblastic and bladder cells; however, this mechanism is disrupted during tumor progression. A prostatic carcinoma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 14 publications
0
18
1
Order By: Relevance
“…These observations appear to contrast earlier reports suggesting a positive relationship between tumor cell motility and metastatic potential (e.g., Mohler et al, 1988). However, an apparent lack of correlation between basal migration of strongly versus weakly metastatic PCa cell lines has been reported and could be related to the distinct patterns of migration undergone by cells of different metastatic abilities (e.g., Silletti et al, 1995). In particular, speed of movement may not be the only variable relevant to malignant cell motility, and other characteristics such as co-ordination (i.e., directionality) of movement may also be an important factor (e.g., Djamgoz et al, 2001).…”
Section: General Aspectscontrasting
confidence: 67%
See 1 more Smart Citation
“…These observations appear to contrast earlier reports suggesting a positive relationship between tumor cell motility and metastatic potential (e.g., Mohler et al, 1988). However, an apparent lack of correlation between basal migration of strongly versus weakly metastatic PCa cell lines has been reported and could be related to the distinct patterns of migration undergone by cells of different metastatic abilities (e.g., Silletti et al, 1995). In particular, speed of movement may not be the only variable relevant to malignant cell motility, and other characteristics such as co-ordination (i.e., directionality) of movement may also be an important factor (e.g., Djamgoz et al, 2001).…”
Section: General Aspectscontrasting
confidence: 67%
“…Cells were plated in 35 mm Petri dishes at an initial density of 15 Â 10 4 cells/dish and allowed to settle for 24 h. Lateral motility was assessed by a monolayer wound assay (Silletti et al, 1995;Peck and Isacke, 1996). Analysis of the closure of the wound was performed as follows.…”
Section: Cellular Motility Assaymentioning
confidence: 99%
“…Previous studies have shown that human and rodent prostate cancer tissues and cell lines produce a variety of autocrine factors [24,28], including epidermal growth factor [22,23,25,26,29], transforming growth factor alpha [22,23,27,30], fibroblast growth factor [31], interleukin 6 [17], androgen-induced growth factor [18], neurotensin [19], parathyroid hormone-related protein [20], insulin-like growth factors I and II [21], and autocrine motility factor [16,32]. In future studies, we intend to identify the various factors produced by prostate cancer cells that regulate energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…To do so, we measured ATP content and migration of MatLu cells grown in conditioned medium with or without added glucose. While conditioned medium from MatLu cells has never been characterized, we hypothesized that MatLu cells produce several autocrine growth factors, as do other prostate cancer cell lines [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Migration and Atp Content Of Cells Inmentioning
confidence: 99%
“…On signal transduction, AMF binds to a cell surface glycoprotein of 78 kDa (19)(20)(21), implying that AMF is the natural ligand of the 78-kDa glycoprotein (17). AMF secreted by Gc-4 PF murine fibrosarcoma cells (10) has PGI activity, whereas rabbit heart PGI can stimulate mouse fibrosarcoma cell motility similar to that of endogenous AMF.…”
mentioning
confidence: 99%